Divergent temporal courses for liking versus wanting in response to persuasion - Joo, Mingyu; Liu, Wendy; Wilbur, Kenneth C (Emotion (Washington, D.C.), 2020)
Liking and wanting are two foundational processes underlying the individual's reward system. Whereas the differences between liking and wanting have been studied extensively in the context of substance addiction, there have been few empirical studies of their manifestation in ordinary, nonaddictive contexts of behavior. In particular, previous research showed a temporal divergence of liking and wanting over repeated exposures to drugs; however, the temporal progression of liking versus wanting in response to ordinary stimuli remains less understood. This research tests the temporal divergence of liking versus wanting responses in a prevalent domain-namely, in response to persuasive messages-using a highly powered field experiment involving over 1,000 real-life stimuli and 100,000 subjects. Subjects were exposed to sequences of TV advertisements in random orderings and indicated how much they liked the persuasive messages and wanted the promoted items. We found, not surprisingly, an overall positive correlation whereby greater message liking was associated with greater wanting of the item. However, underlying the overall correlation, we found a sharp divergence with respect to the serial progression of liking versus wanting. Specifically, message liking was highest early in the sequence, whereas wanting of the promoted item was highest late in the sequence. We posit and provide evidence that this divergence is due to an appetizing effect for wanting, in contrast to a habituation and reference adaptation effect for liking. We discuss the implications of our results for theories of liking versus wanting for addictive as well as ordinary substances. (PsycINFO Database Record (c) 2020 APA, all rights reserved).